Impact of global crisis on social and economic inequality in Medan City: A strategic approach to community empowerment and multi-sector collaboration - Sibero, Bona Manuel Tarigan; Humaizi, Humaizi; Kusmanto, Heri; Ridho, Hatta (Research Journal in Advanced Humanities, 2024)
This research explores the impact of the global crisis on social and economic inequality in Medan City, focusing on social changes triggered by shifts in public policy and external factors affecting community welfare. Through qualitative approaches, this research identifies the main challenges faced by the community, including increased poverty, economic instability, and changes in social structure. The results show that the global crisis has exacerbated social and economic inequality in Medan, significantly impacting access to essential services and economic opportunities. The implications of this research suggest the need for effective data-driven strategies to address inequality, including integrated community empowerment programs and multi-sector collaboration. This research makes a novel contribution to understanding the dynamics of inequality in the context of the global crisis. It offers recommendations for future research, including an emphasis on longitudinal analysis and adaptive policy development. Recommendations for future research include developing more holistic intervention models and evaluating the long-term impact of policies implemented to reduce social and economic inequality.